Personality, Polyculturalism, and Cultural Intelligence: A Cross-Cultural Survey Study - Bernardo, Allan B. I. (Makara Human Behavior Studies in Asia, 2019)
The ability to function effectively in intercultural contexts is increasingly important in our globalized world. This ability has been conceptualized as cultural intelligence (or CQ), and many studies have focused on the factors associated with high CQ. The present study explored personality traits and the lay theory of polyculturalism as factors that predict CQ in two cultural groups (300 Chinese, 247 Filipinos) of university students. The respondents completed a questionnaire that included scales measuring the Big Five personality factors, polyculturalism, and CQ. Hierarchical regression analyses of questionnaire responses from the two samples indicated that consistent with the previous literature, openness to experience and polyculturalism positively predicted CQ in both samples; in addition, emotional stability predicted CQ among the Chinese, and conscientiousness predicted CQ among the Filipinos. The results are discussed in terms of cultural similarities and differences in the experience of CQ.